Probiotic and antimicrobial potential of Enterococcus faecalis CC3 isolated from traditional Vietnamese pickled Brassica juncea - NGUYEN PHUONG THUY; LU THI LAM ANH; NGUYEN THUY LINH; NGUYEN THANH TUU; VUONG TUAN PHONG (Society for Indonesian Biodiversity, 2026)
Abstract. Thuy NP, Anh LTL, Linh NT, Tuu NT, Phong VT. 2026. Probiotic and antimicrobial potential of Enterococcus faecalis CC3 isolated from traditional Vietnamese pickled Brassica juncea. Biodiversitas 27 (2): d270208. https://doi.org/10.13057/biodiv/d270208. Vietnamese pickled mustard greens (Brassica juncea), known as Dua cai muoi chua, harbor diverse microbial communities with potential biotechnological applications. This study aimed to isolate and characterize Lactic Acid Bacteria (LAB) from these traditional pickles to evaluate their probiotic and antimicrobial properties. Sixty samples collected from Vinh Long province, Vietnam, yielded 64 presumptive LAB isolates. These were screened for acid and bile tolerance, antibiotic susceptibility, hemolytic activity, and antimicrobial efficacy against Escherichia coli, Salmonella enterica, and Staphylococcus aureus. Among the candidates, isolate CC3 exhibited superior resilience, maintaining high viability after 12 hours at pH 2.0 and in the presence of 1.0% bile salts. Identified as Enterococcus faecalis via 16S rRNA gene sequencing (GenBank Accession No. PX928037), strain CC3 demonstrated broad-spectrum antimicrobial activity, producing significant inhibition zones against S. aureus (22.59 ± 1.59 mm), E. coli (21.29 ± 1.53 mm), and S. enterica (20.66 ± 1.88 mm). Safety assessments confirmed CC3 as γ-hemolytic (non-hemolytic) and sensitive to clinically relevant antibiotics, including Ampicillin and Chloramphenicol. Furthermore, PCR analysis verified the absence of virulence genes (esp, gelE, cylA, cylM), vancomycin resistance genes (vanA, vanB), and biogenic amine-producing genes (hdc1, hdc2, tdc). These findings highlight the microbial diversity of indigenous fermented vegetables and suggest E. faecalis CC3 as a promising candidate for probiotic applications or as a biopreservative starter culture.